Vasculitis in Clinical Practice - Watts, Richard A.; Scott, David G. I.; Mukhtyar, Chetan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
In this second edition, the authors discuss the newly discovered entity of IgG4 related diseases, look in greater detail at the role of biologic treatment in ANCA associated vasculitis, and have revised the nomenclature in each chapter to reflect international consensus. The addition of illustrations as well as online video content helps the reader manage patients with these potentially devastating conditions. Vasculitis in Clinical Practice, Second Edition, is a useful and concise volume that will help physicians in training, primary care physicians and nurse practitioners in quickly and easily recognizing the key and salient points of each condition.
Part 1. Introduction -- 1. Definitions -- 2. Classification and Epidemiology -- 3. General Presentation of the Vasculitides -- 4. General Principles of Treatment -- Part 2. Features of Individual Diseases -- 5. Giant Cell Arteritis -- 6. Takayasu Arteritis -- 7. Granulomatosis with Polyangiitis - GPA (Wegeners) -- 8. Eosinophilia with Granulomatosis and Polyangiitis- EGPA (Churg–Strauss Syndrome) -- 9. Microscopic Polyangiitis -- 10. Polyarteritis Nodosa -- 11. Kawasaki Disease -- 12. IgA Vasculitis -- 13. Behçet’s Disease -- 14. Cryoglobulinemic Vasculitis -- 15. Vasculitis Mimics -- 16. Secondary Vasculitis -- 17. Primary Angiitis of the Central Nervous System Vasculitis -- 18. Relapsing Polychondritis -- 19. Cogan's Syndrome -- 20. IgG4 Related Disease.
Keywords: Rheumatology; Internal medicine; Allergy; Rheumatology; Internal Medicine; Allergology